Ursachen für das ungleiche Ausreifen von Himbeeren (Thysanoptera: Thripidae; Coleoptera: Byturidae). - Domes, Rüdiger (Contributions to Entomology = Beiträge zur Entomologie, 1957)
1. Some hundred specimens of Frankliniella intonsa Tryb., larvae, praepupae, pupae, and imagines were found in the hollow spaces between fruit and clinanthium of unequal matured raspberries. - 2. The increase of Frankliniella intonsa Tryb. on raspberries culminates in June. - 3. Especially during the culmination of increase there appear suction-injuries on single fruits, which set riping before the time in the course of a few hours. - 4. The sort "Stuttgart" was found to be more seriously infested than the sorts "NZ 55a" and "Schönemann". - 5. Unequal fructescens is attended with increased susceptibility to Botrytis cinerea. - 6. Also cutting and damaging the tissue of ducts by feeding larvae of Byturus tomentosus Fabr. is a cause of the carpels riping before the time as separated from their support of nutrition. - 7. Under conditions as temperature of 23-27°C and support of nutrition artificially interrupted full grown-up carpels are already mature after 4 hours, while undergrown carpels dry up. - 8. Sharp lines between mature and immature carpels indicate injuries being produced by Byturus, in case of diffuse transitions Frankliniella is to be regarded. - 9. Counting out the unequal matured fruits there remained a number of them impossible to explain the cause of their injury.